REALITIES OF TOURIST BUSINESS IN A PANDEMIC CONDITION - Белинская, Кристина; Марусей, Татьяна (SWorldJournal, 2022)
The article considers the issues of modern aspects of the functioning of the tourist sphere of the country. The existing problems of development of the enterprises of the tourist sphere caused by negative influence of development of quarantine restriction